Investigation of sitting position of Paralympic wheelchair basketball players - Akinoglu, B.; Pakoz, B.; Kocanan, T. (Acta of Bioengineering and Biomechanics, 2021)
Purpose: The aim of this study is to examine the sitting position (posture) of wheelchair basketball (WB) players who cannot walk and can walk in daily life and to compare them with the able-bodied sedentary individuals. Methods: A total of 22 male individuals, including six WB players who could not walk in daily life, eight WB players who walked in daily life, and eight able-bodied sedentary individuals (control group) were included in the study. Posture analysis of individuals was evaluated using rastersterographic system DIERS formetric 4D device. Kruskal Wallis test was used to compare the data obtained because of posture analysis. The "Mann Whitney-U" test was used to determine which group caused the difference in the data determined to be different. Statistical significance level was taken as P<0.05. Results: Trunk-length, sacrum-width, sagittal and coronal imbalance, trunk-torsion, pelvicobliqueness, pelvic -torsion, pelvic-inclination and fleche-cervicale were found to be similar in the three groups (P>0.05). It was determined that the lumbar lordosis and thoracic kyphosis angles were different between the groups, and the lumbar lordosis and thoracic kyphosis angles of the WB players who could not walk in daily life were higher than those of the WB players who walked in daily life and the control group (P<0.05). Conclusions: Based on the results of our study, we suggest evaluating the sitting postures of WB players, and rehabilitating WB players, especially those who cannot walk in daily life, with posture corrective exercises aimed at reducing and normalizing thoracic kyphosis.